Assessment of the Influence of the National Bank of Ukraine Monetary Policy on Food Security of the State - Donatello Caruso (Облік і фінанси, 2020)
Food security is central to the state's economic security system and is an important component of its sovereignty. Attracting financial resources by agricultural producers on favorable terms has a direct impact on improving agricultural infrastructure, product quality management systems, modernization of means of production, etc., which contributes to food security in terms of its main components: food availability and food security. At the same time, cheaper consumer loans for the population can strengthen an equally important element of food security – the affordability of food. The object of the study is the processes of food security regulation of the country due to changes in the discount rate of the National Bank. The subject of the study is a set of theoretical, methodical and practical aspects of the monetary policy of the National Bank of Ukraine and their impact on the formation of food security. The purpose of the article is a comprehensive analysis and assessment of the impact of monetary policy of the National Bank of Ukraine, which is recently reflected in lowering the discount rate on food security, which is expressed in the availability of credit resources to meet consumer demand and modernize agricultural enterprises. The analysis of the discount rate and interest rates for loans on different periods, which were given to the enterprises of Ukraine, was performed. The authors propose to improve the financial component of the integrated food security mechanism, which aims to ensure the use of economic levers and create conditions for attracting financial resources for the functioning of the food security system by forming a system of multi-channel financing.